2022
DOI: 10.1111/ajt.16854
|View full text |Cite
|
Sign up to set email alerts
|

Negative immune responses to two-dose mRNA COVID-19 vaccines in renal allograft recipients assessed with simple antibody and interferon gamma release assay cellular monitoring

Abstract: Studies are urgently needed to characterize immunogenicity, efficacy, and safety of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) mRNA vaccines in kidney transplant (KT) recipients, excluded from major clinical trials. Complex ELISPOT and other cellular response techniques have been applied, but simpler tools are needed. An easy‐to‐use real‐world monitoring of SARS‐CoV‐2 IgG antibodies against the Spike protein and QuantiFERON ® SARS‐CoV‐2 IFNγ release assay (IGRA) were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 57 publications
(158 reference statements)
5
68
1
1
Order By: Relevance
“…Overall, 82 studies were included for meta-analysis ( table 1 , supplementary table 2). 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 …”
Section: Resultsmentioning
confidence: 99%
“…Overall, 82 studies were included for meta-analysis ( table 1 , supplementary table 2). 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 …”
Section: Resultsmentioning
confidence: 99%
“…The available data from reports on post-COVID-19 immunity, also supported by those regarding anti-SARS-CoV-2 vaccination, indicate that short time after transplantation, which is an equivalent of a higher immunosuppression burden, is the most important factor responsible for reduced mounting of the anti-SARS-CoV-2 immune response within the first post-transplant months [ 26 ]. Our KTR were median 47, IQR 20–102 months after transplantation, so the immunosuppression-related drawback in a specific immune response may not have been pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that after two doses of mRNA vaccination, >95% of dialysis patients presented anti-S IgG antibodies, while only 63.3% of KTR seroconverted with substantially lower antibody levels. An anti-SARS-CoV-2 cellular response was observed for 77.6% hemodialysis patients and 61.3% of KTR transplanted more than one year ago, while only for 36% of those transplanted within the previous 12 months [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an era of a global pandemic solid organ recipients are particularly vulnerable due to lifelong immunosuppression to prevent allograft rejection. Immunosuppressed solid organ recipients (i) suffer more often from common and opportunistic infections; (ii) infectious diseases tend to have a more severe course and worse outcome compared to non-immunosuppressed patients (10); and (iii) immunosuppressed organ recipients respond less well to vaccines (11)(12)(13). More than 50 years of research since the seminal experiments on chimerism and tolerance performed by Billingham, Brent, and Medawar in the 1950s (14) were required until the first clinical trials were performed for combined kidney and hematopoietic stem cell transplantation from the same living donor (15).…”
Section: Discussionmentioning
confidence: 99%
“…The patients could be vaccinated with the mRNA vaccine BNT162b2, when they were off immunosuppression, and mounted strong and protective neutralizing SARS-CoV-2-specific antibody responses, and 2/3 also specific T cell responses. The number of patients is not sufficient for a conclusive analysis, but the data suggest a better immunological response to the vaccine in comparison to kidney transplant recipients under immunosuppressive therapy (11)(12)(13). This peculiar epidemiological setting, with the opportunity to study in patients the immune response to a novel virus, was instrumental to demonstrate the specificity of the immunological tolerance achieved with this protocol, which allowed acceptance of an allogeneic kidney while maintaining fully protective antivaccine responses.…”
Section: Discussionmentioning
confidence: 99%